Peran dan Strategi Pekerja Sosial Masyarakat Wilayah DKI Jakarta dalam Meningkatkan Kesejahteraan Masyarakat - Muhamad Suharbillah; Azzahra Elvina Sari; Syarifah Hudhriah; Ririn Dwi Prabandari; Khairul Anwar; Wati Nilamsari (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Social empowerment in urban areas such as Jakarta requires local actors who can directly reach communities, especially vulnerable groups. Community Social Workers (PSM) act as strategic partners who connect government programs with real community needs. This Practicum 1 community service activity aimed to strengthen the capacity of PSM through field practice involving students at Dinas Sosial Provinsi DKI Jakarta, particularly in the Social Empowerment Division (Dayasos). The main partners were PSM located in Central Jakarta and South Jakarta. The methods used included community education, training, mentoring, mediation, and direct observation of two main programs: Elderly Meal Support (Pokmas) and Joint Business Groups (KUBE). The results show that systematic empowerment improves PSM’s ability to identify community needs, deliver social services, and strengthen motivation and collaboration. It also increases community participation and faster responses to social issues, helping build sustainable social resilience.